A Review on Microplastic in Freshwater Lake Sediments from Asian Countries: Methods and Abundance - Malla-Pradhan, Rajeshwori; Pradhan, Bijay Lal; Phoungthong, Khamphe; Gyawali, Saroj (BMC Journal of Scientific Research, 2022)
This review paper summarizes the methods used for measuring microplastic in freshwater lake sediments and also compares the distribution and characteristics of microplastic in freshwater lake sediment in Asia. Bulk sampling using Van Veen grab or stainless steel shovel was the most common sampling tool used for sediment sampling. Density separation using sodium chloride (NaCl) is the most common process for the extraction of microplastic from lake sediments. For microplastic quantification, the common preliminary technique is visual counting aided by an optical microscope. Whereas, spectroscopy like Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy is the most commonly used technique for polymer identification. High abundance of microplastic reaching 11 to 3153 items/ kg was observed in the lakeshore sediment of Poyang Lake, China. In the lake bottom sediment of Ulansuhai Lake, the concentration of microplastic was low (24±7 to 14±3 items/kg). Polyethylene and polypropylene was the widely used polymer in Asia.